Macrocycle-Antibiotic Hybrids: A Path to Clinical Candidates - Surur, Abdrrahman Shemsu; Sun, Dianqing (Frontiers in Chemistry, 2021)
The tale of abate in antibiotics continued defense mechanisms that chaperone the rise of drug defying superbugs, on the other hand, the astray in antibacterial drug discovery and development. Our salvation lies in circumventing the genesis of resistance. Considering the competitive advantages of antibacterial chemotherapeutic agents equipped with multiple war-heads against resistance, the development of hybrids has rejuvenated. The adoption of antibiotic hybrid paradigm to macrocycles has advanced novel chemical entities to clinical trials. The multi-targeted TD-1792, for instance, retained potent antibacterial activities against multiple strains that are resistant to its constituent, vancomycin. Moreover, the antibiotic conjugation of rifamycins has provided hybrid clinical candidates with desirable efficacy and safety profiles. In 2020, US FDA has granted an orphan drug designation to TNP-2092, a conjugate of rifamycin and fluoroquinolone, for the treatment of prosthetic joint infections. DSTA4637S is a pioneer antibacterial agent under clinical development and represents a novel class of bacterial therapy, antibody-antibiotic conjugates. DSTA4637S is effective against the notorious persistent S. aureus bacteremia, a revelation of the abracadabra potential of antibiotic hybrid approaches.